Banker's guide to new small business finance, + website : venture deals, crowdfunding, private equity, and technology - Green, Charles H. (Hoboken, New Jersey : Wiley, 2014)
"Detailed, actionable guidance for expanding your revenue in the face of a new virtual marketWritten by industry authority Charles H. Green, Banker's Guide to New Small Business Finance explains how a financial bust from one perfect storm--the real estate bubble and the liquidity collapse in capital markets--is leading to a boom in the market for innovative lenders that advance funds to small business owners for growth. In the book, Green skillfully reveals how the early lending pioneers capitalized on this emerging market, along with advancements in technology, to reshape small company funding. Through a discussion of the developing field of crowdfunding and the cottage industry that is quickly rising around the ability to sell business equity via the Internet, Banker's Guide to New Small Business Finance covers how small businesses are funded; capital market disruptions; the paradigm shift created by Google, Amazon, and Facebook; private equity in search of ROI; lenders, funders, and places to find money; digital lenders; non-traditional funding; digital capitol brokers; and much more. Covers distinctive ideas that are challenging bank domination of the small lending marketplace Provides insight into how each lender works, as well as their application grid, pricing model, and management outlook Offers suggestions on how to engage or compete with each entity, as well as contact information to call them directly Includes a companion website with online tools and supplemental materials to enhance key concepts discussed in the book If you're a small business financing professional, Banker's Guide to New Small Business Finance gives you authoritative advice on everything you need to adapt and thrive in this rapidly growing business environment"--
"This book provides active suggestions of how baking professionals can protect their client base and also expand their revenue in cooperation with alternative financing entities"--
Part I: Survey of funding small business -- How small businesses are funded -- Elusive nature of bank Funding -- Capital market disruptions, post-2008 -- Part II: a perfect storm rising -- A paradigm shift created by Amazon, Google, and Facebook -- Private equity in search of ROI -- First change the marketplace, then change the market -- Part III: digital dynamics in small business funding -- Funders and lenders -- online capital providers -- Crowdfunding with donors, innovators, loaners and shareholders -- Other innovative funding sources on the rise -- Capital guides -- online resources to find, coach and assist borrowers/lenders -- What innovation means for bank lending.
Includes index.
Print version record and CIP data provided by publisherd.
Includes bibliographical references and index.
Keywords: Small business -- Finance; Banks and banking; Small business -- Finance; Banks and banking; BUSINESS & ECONOMICS -- Banks & Banking; Banks and banking; Small business -- Finance; Small business / Finance; Banks and banking; Electronic books